Efficiency Of Think-Tankâ€™s Policy Recommendations In Turkey: Case Of Kurdish Issue - Celikturk, Tanzer (European Scientific Journal, ESJ, 2016)
A think-tank can be defined as "governments in the waitingâ€. These organizations have interest in many different areas of public problems and employ a variety of expertise to comprehend problems in all perspectives. The aim of a think-tank is to create trustworthy knowledge and alternative solutions about social problems depending on empirical data. But there is a problem about measuring the effectiveness of policy recommendations. One of the measures is watching over the effect on policy outputs. In this work, i try to put forward the effectiveness of policy recommendations which were formulated by prominent think-tank and non-governmental organizations in Turkey within the case of Kurdish Issue. I will handle and analyse the policy outputs to measure the effectiveness of policy recommendations within the scope of laws, enactments and regulations in relation to Kurdish Issue.